GPR37 modulates body weight and insulin sensitivity in a sex-biased manner - Mariam Ahmed; Mariela Nunez Santos; Karen Abdelsayed; Corrine Liu; Nimco Xuseen; Pokuaa Adwoa Boakye; Sharon Owino (PLoS ONE, 2026)
Metabolic disorders are a growing public health concern in the United States, with approximately 40% of the population living with obesity. The urgent need for novel therapeutic targets has driven interest in G protein–coupled receptors (GPCRs), a diverse group of seven-transmembrane receptors that regulate various physiological processes and represent a significant portion of current drug targets. In this study, we investigated the role of GPR37, a brain-enriched orphan GPCR, in systemic glucose regulation. Using heterozygous Gpr37 + /- mice, we assessed body weight, glucose tolerance, and insulin sensitivity. Male Gpr37 + /- mice exhibited significantly reduced body weight, an enhanced metabolic response to fasting, and increased insulin sensitivity compared to wild-type controls. These findings indicate that reduced Gpr37 gene dosage is associated with metabolic efficiency, particularly in the regulation of glucose metabolism, and reveal a previously unrecognized sex-biased role for GPR37 in systemic energy homeostasis. Taken together, these data suggest that GPR37 contributes to metabolic regulation and represents a candidate pathway for further pharmacological and tissue-specific study.